2009
DOI: 10.1002/anie.200900802
|View full text |Cite
|
Sign up to set email alerts
|

Gold Supported on Hydroxyapatite as a Versatile Multifunctional Catalyst for the Direct Tandem Synthesis of Imines and Oximes

Abstract: Two birds with one auric stone: The title system acts as a highly efficient heterogeneous catalyst for the one-pot tandem synthesis of imines or oximes from alcohols and the corresponding amines under mild conditions (see scheme; HAP = hydroxyapatite).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
124
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 267 publications
(127 citation statements)
references
References 66 publications
3
124
0
Order By: Relevance
“…During the course of our investigation, the sequential one-pot synthesis of secondary amine in Scheme 1a by Au/TiO 2 and Au/C was demonstrated by Grirrane et al (12) and the one-pot synthesis of imine in Scheme 1b by Au/hydroxyapatite was reported by Sun et al (13). However, the effect of the size of Au NPs on the reactions was studied only for the first oxidation step by using Au NPs larger than 3.5 nm.…”
Section: Introductionmentioning
confidence: 62%
“…During the course of our investigation, the sequential one-pot synthesis of secondary amine in Scheme 1a by Au/TiO 2 and Au/C was demonstrated by Grirrane et al (12) and the one-pot synthesis of imine in Scheme 1b by Au/hydroxyapatite was reported by Sun et al (13). However, the effect of the size of Au NPs on the reactions was studied only for the first oxidation step by using Au NPs larger than 3.5 nm.…”
Section: Introductionmentioning
confidence: 62%
“…They obtained excellent yields of imines from a variety of aryl or alkyl starting materials (Table 11). 156 In 2006, Angelici et al reported that bulk gold could catalyze the oxidative coupling of isocyanides with primary or secondary amines to give carbodiimides or urea as products under mild reaction conditions (Scheme 18). 157 In the reactions of n-BuNC, HN(nPr) 2 , and O 2 at 60 C as catalyzed by gold powder, they obtained over 70% yield of the urea after 72 h reaction.…”
Section: Introductionmentioning
confidence: 98%
“…Supports usually used are oxides, such as TiO 2 , Al 2 O 3 , CeO 2 , SiO 2 , and ZrO 2 . However, metal salts have been seldom used as supports for making gold catalysts [9][10][11][12][13][14][15][16][17][18][19][20]. Our group recently developed an array of metal phosphate-based gold catalysts by deposition-precipitation [21].…”
Section: Introductionmentioning
confidence: 98%